Dual-cathode plasma-induced exfoliated WSe2/graphene nanosheet composite mediating an efficient hydrogen evolution reaction. (20th April 2023) - Hsiao, Chang-Yu; Dang, Van Dien; Hsu, Ya-Wen; Lu, Yi-Ting; Hsu, Pei-Ju; Le, Phuoc Anh; Wei, Kung-Hwa
Abstract: With the goal of obtaining a sustainable earth-abundant electrocatalyst that displays high performance in the hydrogen evolution reaction (HER), herein we describe a new electrochemical process for the simultaneous dual-cathodic plasma-induced exfoliations of two different bulk materials—graphite and WSe2 —into two-dimensional (2D) nanosheets for the fabrication of a homogeneous composite. Using this approach, we produced unique structures of graphene nanosheet-engulfed ultrathin WSe2 nanosheets (WSe2 @GN), stabilized through van der Waals and π–π interactions between the WSe2 and GNs, possessing various morphologies and featuring large edge and defect densities on the basal plane of the GNs—potential active sites for HER catalysis. This synthesis of WSe2 @GN structures not only increased the number of active sites in the semiconducting WSe2 nanosheets but also enhanced their conductivity. Our dual-cathode plasma produced WSe2 @GN nanosheet composites exhibited high HER performance, characterized by a low overpotential of 106 mV at a current density of 10 mA cm –2, a Tafel slope of 66 mV dec –1, and long-term stability in 0.5 M H2 SO4 (80% activity retention after >48 h); these performance metrics were much better than those of the corresponding WSe2 /GN composite, prepared through two sequential single-cathode electrochemical plasma exfoliation and mixed together (233 mV, 111 mV dec –1 ), and are among the best ever reported for a composite involving WSe2 and GNs, prepared through simultaneous exfoliation at a low temperature and over a short period of time, for the HER. This in situ dual-plasma-exfoliation synthetic approach allows the effective production of homogeneous 2D/2D heterostructures with great potential for various energy-related applications, while being an effective and simple strategy for tuning the morphologies of composites of graphene and transition metal dichalcogenide materials for a broad range of energy applications. Graphical abstract: Image, graphical abstract